Quiz. Correct answer to the quiz. Check your diagnosis Histiocytic necrotising lymphadenitis in mediastinum mimicking thymoma or lymphoma – case presentation and literature review of Kikuchi Fujimoto disease - Błasiak, Piotr; Jeleń, Michał; Rzechonek, Adam; Marciniak, Marek; Pawełczyk, Konrad; Cianciara, Jan; Kołodziej, Jerzy; Muszczyńska-Bernhard, Beata (Polish Journal of Pathology, 2016)
Kikuchi Fujimoto disease (KFD) as a rare self-limiting lymphadenopathy of short and benign course concerns most frequently the lymph nodes of the neck. The most common symptoms are painfulness of the diseased area, fever and night sweating. The etiology is not well understood, but in the role of pathogenesis viral, autoimmune and genetic factors are taken into account. In the presented case of 37-year-old female it was necessary to exclude diseases such as lymphoma or thymoma because of atypical mediastinal location of Kikuchi Fujimoto disease. After multidisciplinary consultation the lymph node was resected from the mediastinum with videothoracoscopic approach. The diagnosis was difficult for the pathologist because of the large percentage of necrosis of the lymph node but the image was typical for histiocytic necrotizing lymphadenitis. Two cases of patients with KFD limited to the mediastinum have been previously reported in the literature. This article presents the world’s first reported case of this disease in the topographic location of the thymus. Furthermore, a review of current literature was made.